The symbols and interpretants of beetle and flower in the Malay Pantun - Hassan, Noor Roza; Mohd Kiram, Norazlina; Zainal Abidin, Zairul Fakhri (Human Resource Management Academic Research Society, 2022)
This paper discusses the symbols and interpretants of young man (teruna) and young woman (dara) that are indirectly expressed in the traditional Malay pantun. Beetle (kumbang) and flower (bunga) as the symbols and interpretants are selected for the discussion because these two symbols are often presented simultaneously in the meaning part of the pantun. Both symbols and interpretants, like other symbols, imply a conventional meaning. The implicit meaning is shared by the poet who creates the pantun and the listener. Therefore, when a symbol is mentioned in a pantun, the listener knows its meaning. The conventional meaning of symbols and interpretants in the pantun is compatible with the pantun itself as a poetic communication tool in life. Thus, the pantun is different from the modern poetry that uses symbols and interpretants which are more personal and requires the readers to imply the meaning. In the pantun, the symbols with their conventional meanings help the listeners to understand something related to the symbols and interpretants. Hence, beetle and flower with the meaning of a young man and a young woman that are expressed in the quatrain (four lines) pantun which is the most popular traditional pantun among the traditional Malay community will be discussed.